Technology improvement for manufacturing and repair of collapsible pipelines - Матвієнків, Олег Михайлович (Technology audit and production reserves, 2016)
Application of arc brazing technology for manufacturing and repair of collapsible pipelines to replace arc MIG/MAG welding was proposed. The use of this technology to connect galvanized elements of collapsible pipelines preserving the protective coating in the joints was analyzed and justified. Strength of samples of welded and brazed joints, galvanized pipes, collapsible field pipelines by tear test was investigated and strength characteristics of joints defined by measuring the hardness of a section connections was defined. It was found that joints made by arc brazing by CuAl8 filler rod have the strength level of the welded joints. Due to the small thermal effects, with arc brazing, there is no destruction of the protective zinc coating at the joint place. Research results allow recommending arc brazing technology by CuAl8 filler for manufacturing and repair of collapsible pipelines, preserving strength joints without destruction of the protective zinc coating at the joint place.